Pengaruh Modernisasi terhadap Pemeliharaan Tanah Ulayat di Minangkabau - Luwes Dwi Triani; Dean Power Saragih; Muhammad Aldo Savero; Achmad Rizky Airlangga; Nanjelina Adinda Fazya; Aqila Husna; Agung Widya Setya Pratama (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This journal discusses the influence of modernization on the management and maintenance of Minangkabau customary land. Modernization itself is a change that occurs over time. Its relationship with humans is how humans adapt to all changes to meet all their life needs. Customary land management is carried out by traditional communities by following the laws that apply in the community or often called customary law. With modernization, existing laws in the community and updated laws will adapt to each other, because laws exist for humans, not humans for the law. The main topic of discussion is how the modernization system applies to Minangkabau land management and what influence modernization has on Minangkabau land management. The existing data to answer this main problem is empirical data originating from journals, books, or applicable laws and regulations.